Implementasi Perpres Nomor 81 Tahun 2010 tentang Reformasi Birokrasi di Sekretariat Daerah Provinsi Jawa Tengah - Gatot Satria Pamungkas; Sulistyowati . . (Journal of Politic and Government Studies, 2017)
ABSTRACT Implementation of policies Reforms in Central Java Provincial Secretariat stipulated in Presidential Decree Number 81 Year 2010 About Reforms in Central Java Provincial Secretariat for guidelines to strengthen the accountability framework and establish a system of integrity in local governance. Reforms are also needed to face the globalization era. This research is a descriptive qualitative research that describes in depth on the Implementation of Presidential Decree No. 81 Year 2010 About Reforms in Regional Secretariat of Central Java province. And wanted to explain the factors driving and inhibiting and what efforts were undertaken Regional Secretariat of Central Java province in implementing Presidential Decree No. 81 Year 2010 About Reforms. Data collection techniques in this study using interviews and document study. From the research it can be concluded that the implementation of Presidential Decree No. 81 Year 2010 About Reforms in Regional Secretariat of Central Java province has been carried out properly and optimally. Regional Secretariat of Central Java province has been doing the structuring and strengthening of some areas, among others: the organization, the regulation, legislation, human resources personnel, oversight, accountability, public service and mindset and work culture. Nevertheless there are still areas that have not implemented the changes properly and optimally yan due to limited budget you have. Central Java Provincial Secretariat should attempt to communicate actively with the legislature to improve and accelerate the process of the budget in the following year. Keywords: Implementation, Reforms, the Regional Secretariat of Central Java Province